Differentiated Project Based Learning Model: An Effective Strategy in Ecoliteracy Education for Elementary School Students - Nina Rahayu; Sekar Purbarini Kawuryan; Garib Firman Buaga (Jurnal Penelitian Pendidikan IPA, 2025)
Increasingly complex environmental problems demand strategic efforts in shaping ecological awareness and behavior from an early age. In this context, basic education has a strategic role in internalizing ecoliteracy values through appropriate learning approaches. This study aims to analyze the effect of the Differentiated Project Based Learning (PjBL) Model on improving the ecoliteracy skills of fifth grade elementary school students. The study used an experimental design with control and experimental groups totaling 31 students each. The pretest results showed that the average ecoliteracy ability of the experimental group was 64.03, while the control group was 66.68. After the application of Differentiated PjBL, the posttest showed that the average ecoliteracy ability of the experimental group increased to 75.32, while the control group was 70.35. The independent sample t test showed a significant difference in the posttest between the two groups (p = 0.039 < 0.05), and the paired t test in the experimental group also showed a significant improvement (p = 0.000 < 0.05). Thus, it can be concluded that the application of the Differentiated PjBL Model can significantly improve the ecoliteracy skills of fifth grade elementary school students and is more effective than conventional learning methods.